Central bank digital currency in an open economy - Massimo Minesso Ferrari; Arnaud Mehl; Livio Stracca (European Central Bank (ECB), 2020)
We examine the open-economy implications of the introduction of a central bank digital currency (CBDC). We add a CBDC to the menu of monetary assets available in a standard two-country DSGE model with financial frictions and consider a broad set of alternative technical features in CBDC design. We analyse the international transmission of standard monetary policy and technology shocks in the presence and absence of a CDBC and the implications for optimal monetary policy and welfare. The presence of a CBDC amplifies the international spillovers of shocks to a significant extent, thereby increasing international linkages. But the magnitude of these effects depends crucially on CBDC design and can be significantly dampened if the CBDC possesses specific technical features. We also show that domestic issuance of a CBDC increases asymmetries in the international monetary system by reducing monetary policy autonomy in foreign economies.
Keywords: E50; F30; 330; Central bank digital currency; DSGE model; open-economy; optimal monetary policy; international monetary system